Effect of catalyst contact on the pyrolysis of wheat straw and wheat husk. (15th November 2015) - Krishna, Bhavya B.; Singh, Rawel; Bhaskar, Thallada
Highlights: Thermal and catalytic slow pyrolysis of wheat straw and husk has been carried out. Different zeolite catalysts have been screened for catalytic pyrolysis. Catalyst mode of contact is an important reaction parameter in pyrolysis. Product distribution is different in every case as decomposition mechanism varies. Abstract: Slow pyrolysis of wheat straw and wheat husk has been carried out using microporous zeolite catalysts such as H-ZSM-5, mordenite and Y zeolite. Catalyst testing has been carried out at two positions in the reactor; one where it is mixed with the feed and other, by placing it in a catalyst boat to allow vapour phase contact. The thermal experiments have been carried out at 300, 350, 400 and 450 °C and the catalytic experiments have been carried out at 350 °C. Bio-oil yields are lower in all cases of catalytic pyrolysis of wheat straw compared to thermal run. With wheat husk, most cases of catalytic pyrolysis produced more bio-oil than thermal run. The bio-oil has been characterised using Gas Chromatography–Mass Spectrometry (GC–MS) and 1 H Nuclear Magnetic Resonance ( 1 H NMR) and bio-char using Fourier Transform-Infra Red spectroscopy (FT-IR), X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). It has been observed that the pyrolysis product profile and decomposition mechanism is dependent on the method of contact of catalyst.